PENGARUH LATIHAN QUICK LEAP TERHADAP POWER OTOT TUNGKAI TIM BOLA VOLI PUTRA SMP NEGERI 13 PEKANBARU - Sembiring, Bredi Ananda; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this research is "The effect of quick jump exercises on leg muscle in the Pekanbaru 13 men's salley team?" So that athletes can perform and play much better in the future and especially after research and find out if there is an increase in leg muscle athlete strength in volleyball games to balance the opponent's game and achieve maximum results in the future. The form of this research is (using the only group of pre-test post-test design approach), with the population of volleyball players in the Pekanbaru 13 Junior High School. The data in this research are all populations of 8 people. The instrument used in this research used the Vertical Jump test, which aims to determine the effect of rapid jump training on leg muscle strength on the volleyball team of the Pekanbaru 13 Junior High School. The data were then processed with statistics to test the normality using the lilifours test at a significant level of α = 0,05. The proposed hypothesis is that the volleyball team of the Pekanbaru 13th Junior High School jumps fast when training on the leg muscles. Based on the normal test analysis, data X produces Lcount of 0.1717 and Ltable of 0.285, which means Lcount < Table. While Y-variable produces Lcount equal to 0.1590 and Ltable equals 0.285. This means Lcount <LTable. There are averages based on the analysis of statistical data variable X 16.87 and the average variable Y is 18.10, then the data is normally distributed. There is, for example, the effect of Quick Leap exercises on the leg muscle strength of the Pekanbaru 13 Public Junior High School residency volleyball team.Key Words: Quick Leap exercises, Strength of leg muscle